Implementasi Algoritma Weighted Sum Model dalam Sistem Penjaminan Mutu Perguruan Tinggi - Ryan Fitrian Pahlevi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The Indonesia government implements a Quality Assurance System (QAS) of a Higher Education (HE) for realizing the quality education. Muhammadiyah manages several Muhammadiyah/’Aisyiyah College (MAC) with SPM Business Processes Management (BPM) as a form of achieving the quality of a National Higher Education Standards. A Quality Assurance (QA) of the HE is set in a Quality Standards (QS). The number of criteria and relationships with the QA activities become an issue which is appointed in this research. The research is focused on the analysis of the decision-making method Weighted Sum Model (WSM) in the Decision Support System (DSS). The research objective is the use of decision-making methods in the form of DSS using the WSM algorithm and testing the use of these algorithms in the implementation of the QAS in MAC. The WSM algorithm is used and tested on a quality standard database with comparison variables between methods, namely relevance, characteristics, accuracy, precision, reliability, effectiveness, efficiency, strength, and weaknesses.The results and analysis of the research is the use of the WSM algorithm to determine the priorities of the 11 HE Business Processes to inform PTMA Leaders in predicting strategic activities. The analysis process has been carried out and it is found that the WSM algorithm is used in the PTMA SPM with a test assessment score of 94%. Keywords - Quality Assurance System (QAS), Decision Support System (DSS), Muhammadiyah/’Aisyiyah College (MAC), Quality Standard.